Buddhist meditation for vascular function: a narrative review - Anjalee Thanuja Amarasekera; Dennis Chang (Integrative Medicine Research)
Background: High blood pressure represents an important risk factor for diseases related to cardiovascular system and is directly associated with high oxidative stress, inflammation and vascular endothelial dysfunction. Recently, there is promising data available to suggest that meditation-based low-cost and low-risk lifestyle modification strategies may provide beneficial effects on chronic inflammation, oxidative stress and maintenance of blood pressure, both in young and older adults. This review aims to summarize the evidence regarding the effectiveness of Buddhist meditation for vascular endothelial function and blood pressure. Method: A search was conducted using Ovid MEDLINE, Scopus, CINAHL and PsycINFO for articles published from 1990 to 2018. Results: Relevant articles (n = 407) were reviewed and 5 met selection criteria. Several lines of studies have provided compelling data showing that Buddhist meditation approach was effective in improving inflammation and vascular function (endothelial vasodilation and arterial stiffness) in both young and elderly cohorts. Particularly, Buddhist meditation approach has shown to be effective in reducing plasma inflammatory markers, increasing nitric oxide concentration and improving vascular endothelial function and glycemic control, which in turn can be favorable factors for demonstrated positive effects of Buddhist meditation on blood pressure and vascular function. Conclusion: This paper presents brief overview of clinical outcomes of complementary therapeutic approach of Buddhist meditation in vascular function. In future, well-structured systematic reviews are essential to report specificity of Buddhist mindfulness-based approach on vascular function, blood pressure and other cardiovascular risk factors. Keywords: Hypertension, Buddhist meditation, Vascular endothelial function, Inflammation, Breathing meditation